1984
DOI: 10.2307/1942501
|View full text |Cite
|
Sign up to set email alerts
|

Carbon and Nitrogen Dynamics During the Decomposition of Litter and Roots of a Chihuahuan Desert Annual, Lepidium Lasiocarpum

Abstract: Carbon and nitrogen dynamics were analyzed during the decomposition of litter and roots of the desert ephemeral pepperweed (Lepidium lasiocarpum). We treated litter bags with the insecticide chlordane and the fungicides benomyl and captan to eliminate or restrict groups of soil biota.The mass losses of buried litter (51, 39, and 25% for untreated, insecticide-treated, and fungicideinsecticide-treated material, respectively) were higher than those of the respective root treatments (35, 18, and 15%) at 96 d. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
2

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 159 publications
(72 citation statements)
references
References 41 publications
3
67
2
Order By: Relevance
“…Whitford et al, 1982;Silva et al, 1985) suggest that the moisture insensitivity of decay of surface litter in the Jornada Basin is due to termites or other microarthropods transporting the material into the soil pool. When microarthropods and/or termites were removed, rates of mass loss from bags of leaf litter were reduced substantially Parker et al, 1984b), and the resulting mass loss was much more strongly related to levels of soil moisture (Whitford & Parker, 1989). However, we saw no obvious evidence of termite activity in the litter samples, and furthermore, the increase in the N content of the remaining litter, that we observed in both control and treatment litter during the first half of the study (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Whitford et al, 1982;Silva et al, 1985) suggest that the moisture insensitivity of decay of surface litter in the Jornada Basin is due to termites or other microarthropods transporting the material into the soil pool. When microarthropods and/or termites were removed, rates of mass loss from bags of leaf litter were reduced substantially Parker et al, 1984b), and the resulting mass loss was much more strongly related to levels of soil moisture (Whitford & Parker, 1989). However, we saw no obvious evidence of termite activity in the litter samples, and furthermore, the increase in the N content of the remaining litter, that we observed in both control and treatment litter during the first half of the study (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…However, some decomposition studies have been performed in arid and semi-arid ecosystems with extreme ranges of moisture availability and many other climatic factors, mostly in North American deserts (Elkins & Whitford, 1982;Parker et al, 1984;Schaefer et al, 1985;Whitford et al, 1988), with only a few studies in the Negev Desert of Israel Steinberger et al, 1990). The North American studies, especially those conducted in the Chihuahuan Desert, have elucidated several surprising features of the decomposition rate in deserts: (1) the rate of organic matter decomposition is high and almost equal to that reported for the wet tropics (Schaefer et al, 1985); (2) the rate of decomposition is not correlated with lignin content or actual evapotranspiration (Whitford et al, 1981;Santos et al, 1984;Schaefer et al, 1985); (3) there is no relationship between the litter decomposition rate and litter quality (Schaefer et al, 1985); and (4) soil fauna accelerate the decomposition of buried litter but not surface litter (Parker et al, 1984). In addition, Berg (1984) and Offer et al (1992) suggested the possibility that soil nutrients, especially nitrogen, may play an important role in controlling the litter decomposition rate.…”
Section: Introductionmentioning
confidence: 99%
“…The higher soil nitrogen on plots with no straw mulch and no termites resulted from the decomposition and mineralization of annual plant roots (Parker et al, 1984). Subterranean termites consume a large fraction of annual plant roots .…”
Section: Discussionmentioning
confidence: 96%